Nutritional Composition of Wild Edible Mushrooms Scleroderma cepa and Laccaria laccata - Jha, Sanjay Kumar; Thapa, Swastika (Journal of Nepal Biotechnology Association, 2025)
Wild edible mushrooms are widely recognized for their high nutritional value and used as food. This study analyzed the macronutrient and mineral composition of Laccaria laccata and Scleroderma cepa, focusing on moisture, ash, protein, fiber, fat, carbohydrate, calcium, phosphorus and iron. The quantitative estimation of these components was conducted using standard analytical techniques: oven-dry method for moisture, Soxhlet extraction for fat, Kjeldahl digestion for protein, ignition method for ash, proximate analysis for carbohydrates, acid-base digestion for crude fiber, complexometric titration for calcium, molybdenum blue method for phosphorus, and colorimetric analysis for iron. The results revealed that carbohydrates were the most abundant macronutrient (54.93–60.42%), while fat was present in the low amount (0.38–0.55%). Among the minerals, phosphorus content ranged from 424.9 to 507.72 mg/100 g, calcium from 182.83 to 243.16 mg/100 g, and iron from 43.25 to 48.14 mg/100 g. These findings highlight the nutritional significance of these wild edible mushrooms reinforcing their potential as valuable dietary food supplements.